High propensity of membrane fouling and the underlying mechanisms in a membrane bioreactor during occurrence of sludge bulking. (1st February 2023) - Wu, Mengfei; Zhang, Meijia; Shen, Liguo; Wang, Xinhua; Ying, Deng; Lin, Hongjun; Li, Renjie; Xu, Yanchao; Hong, Huachang
Highlights: Membrane bioreactor (MBR) operated in sludge bulking stage suffered serious fouling. Bulking sludge had a higher specific filtration resistance (SFR) of five times than normal sludge. Microbial community transition was responsible for the occurrence of sludge bulking. Bulking sludge had an adhesion propensity of 3.6 times than normal sludge. XDLVO and Flory-Huggin's theory gave explanations for the membrane fouling of bulking sludge. Abstract: While sludge bulking often occurring in activated sludge processes generally leads to serious membrane fouling in membrane bioreactors (MBR), the underlying causes are still unclear. In this study, fouling behaviors of a MBR operated at stages of normal and sludge bulking were compared, and the fouling mechanisms of the different behaviors were explored. It was found that, the MBR could be stably operated in normal stage without membrane cleaning for about 60 days, whereas, daily membrane cleaning had to be carried out when operated in sludge bulking stage. The bulking sludge possessed a rather high specific filtration resistance (SFR) of about 1.36×10 14 m·kg −1, which is over 5.33 times than that of the normal sludge. A series of characterizations demonstrated that the bulking sludge had rather lower dewaterability, smaller particle size, higher fractal dimension, higher viscosity, abundant filamentous bacteria and different functional groups of extracellular polymer sustains (EPS). It was suggested that microbial community transition was responsible for the occurrence of sludge bulking, further affecting membrane fouling. Based on these characterizations, it was reported that adhesion propensity (indicated by the thermodynamic interaction) of the bulking sludge to the membrane surface is about 3.6 times than that of the normal sludge. It was proposed that, extra force should be provided to offset a chemical potential gap caused by foulant layer structure transition during sludge bulking in order to sustain filtration of the bulking sludge, resulting in extremely high SFR. This study offered deep thermodynamic mechanisms of MBR fouling during occurrence of sludge bulking. Graphical abstract: Image, graphical abstract